2022
DOI: 10.2105/ajph.2022.306973
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-Associated Shifts in SARS-CoV-2 Infectivity Among the Native Hawaiian and Other Pacific Islander Population in Hawaii

Abstract: Native Hawaiians and other Pacific Islanders (NHPIs) across the country have experienced significant disparities because of the COVID-19 pandemic. The Pacific Alliance Against COVID-19 used a community-based participatory approach involving academic and community partners to expand sustainable COVID-19 testing capacity and mitigate the severe consequences among NHPI communities in Hawaii. We describe the approach of this one-year study, some of the results, and how the data are being used to inform next steps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, how these factors interact to influence an individual's decision about vaccination is not fully understood. This is particularly important in Hawaii, especially for the severely under-vaccinated Native Hawaiian population, where trust in the government has been historically problematic [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, how these factors interact to influence an individual's decision about vaccination is not fully understood. This is particularly important in Hawaii, especially for the severely under-vaccinated Native Hawaiian population, where trust in the government has been historically problematic [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The Community-Driven Approach to Mitigate COVID-19 Disparities in Hawai’i’s Vulnerable Populations: May Okihiro (Department of Pediatrics), Ruben Juarez (Department of Economics) and Alika Maunakea (Department of Anatomy, Biochemistry & Physiology) received pilot funds to assess COVID-19 vaccine hesitancy among vulnerable adults living in Hawai‘i [ 29 ]. The investigators assembled a multidisciplinary team of academic and community investigators, along with long-standing community partners across Hawai‘i, to form a collaborative called the Pacific Alliance Against COVID-19 (PAAC) to participate in the National Institutes of Health Rapid Acceleration of Diagnostics-Underserved Populations (RADx-UP) Initiative [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, it is worth noting that Indigenous populations exhibited lower vaccine intention in studies conducted in 2020 (Ogilvie et al, 2021 ; Tang et al, 2021 ). With respect to other Indigenous populations worldwide, Native Americans/Alaskan natives had the highest vaccine refusal rate and the lowest level of institutional trust (Bagasra et al, 2021 ), and Native Hawaiian and other Pacific Islander populations demonstrated low vaccine uptake due to lack of trust in COVID-19 information (Juarez et al, 2022 ), indicative of low vaccine intention among these populations.…”
Section: Discussionmentioning
confidence: 99%